2022
DOI: 10.5588/ijtld.21.0632
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of asynchronous VOT among patients with MDR-TB

Abstract: BACKGROUND: We conducted a feasibility and acceptability study of video-observed therapy (VOT) among patients with multidrug-resistant TB (MDR-TB) and other types of drug-resistant TB (DR-TB) in the Philippines.METHODS: Patients aged ≥13 years were approached to use VOT. A smartphone with VOT mobile application to video-record medication intake was provided. Healthcare workers (HCWs) monitored adherence by watching videos via a web-based dashboard. Good adherence was defined as intake of >90% of expected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Another common measure of effectiveness was treatment completion as defined by the WHO 76 , which was reported as higher with VOT than DOT in various studies 8,27,44 . Comparable treatment completion rates with VOT versus DOT were reported in other studies 4,26,28,36,47,68,71,76 . No study reported treatment completion rates to be worse amongst people using VOT compared to DOT but, notably, none were specifically designed to demonstrate treatment completion inferiority or superiority.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Another common measure of effectiveness was treatment completion as defined by the WHO 76 , which was reported as higher with VOT than DOT in various studies 8,27,44 . Comparable treatment completion rates with VOT versus DOT were reported in other studies 4,26,28,36,47,68,71,76 . No study reported treatment completion rates to be worse amongst people using VOT compared to DOT but, notably, none were specifically designed to demonstrate treatment completion inferiority or superiority.…”
Section: Resultssupporting
confidence: 63%
“…Treatment success was higher amongst people with TB using VOT than DOT in one study 26 , but comparable between VOT and DOT in other studies 36,52,55,64 . Culture conversion rates for VOT were similar to DOT in three studies 37,52,71 .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…However, there are also local factors which further shape overall costs such as the cost of internet and SMS, the DAT and platform used, specific infrastructure used and patient population served, labor costs and treatment duration. There remain important barriers beyond widespread internet connectivity and infrastructure: these include limited availability, accessibility, and affordability of some technologies for persons in resource-limited areas, and similarly the availability and affordability of technical personnel needed to support the TB clinics (22, 33). Hence real-world cost, effectiveness, and implementation data from high TB-incidence, lower-income settings will remain paramount.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate the effectiveness of the DATs. This has been addressed in other related publications and an analysis of the feasibility and acceptability of DATs in the TB REACH projects is forthcoming (22). The technologies themselves have recognized limitations: for example, messages received or not received by the 99DOTS platform do not necessarily equate with medication ingestion, or lack thereof (23,24).…”
Section: Discussionmentioning
confidence: 99%